2017
DOI: 10.1080/09658211.2017.1282968
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine cravings impair memory and metacognition

Abstract: Cravings for food and other substances can impair cognition. We extended previous research by testing the effects of caffeine cravings on cued-recall and recognition memory tasks, and on the accuracy of judgements of learning (JOLs; predicted future recall) and feeling-of-knowing (FOK; predicted future recognition for items that cannot be recalled). Participants (N = 55) studied word pairs (POND-BOOK) and completed a cued-recall test and a recognition test. Participants made JOLs prior to the cued-recall test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…That is, compared to those in the placebo condition, alcohol-intoxicated individuals had poorer ability to discriminate between their correct and incorrect emotion recognition decisions, indicating a reduced level of insight into their emotion perception ability. These findings are consistent with previous research from the memory literature showing that manipulations that reduce decision accuracy can also reduce resolution for metacognitive judgments (e.g., Bothwell et al, 1987; Deffenbacher, 1980; Hertzog et al, 2010; Palmer, Sauer, Ling, & Riza, 2017). These effects are also consistent with the notion that alcohol intoxication reduces the quality of information that participants are able to draw on when making confidence judgments about the accuracy of their emotion recognition decisions.…”
Section: Discussionsupporting
confidence: 91%
“…That is, compared to those in the placebo condition, alcohol-intoxicated individuals had poorer ability to discriminate between their correct and incorrect emotion recognition decisions, indicating a reduced level of insight into their emotion perception ability. These findings are consistent with previous research from the memory literature showing that manipulations that reduce decision accuracy can also reduce resolution for metacognitive judgments (e.g., Bothwell et al, 1987; Deffenbacher, 1980; Hertzog et al, 2010; Palmer, Sauer, Ling, & Riza, 2017). These effects are also consistent with the notion that alcohol intoxication reduces the quality of information that participants are able to draw on when making confidence judgments about the accuracy of their emotion recognition decisions.…”
Section: Discussionsupporting
confidence: 91%
“…While many studies suggest that caffeine produces improvement in memory either in animal (Munawar, 2022;Villanueva-Garcia et al, 2020) or in human (Borota et al, 2014;Sherman et al, 2016;Hartney, 2020) models of learning and memory, other studies report that caffeine does not affect memory (Nehlig, 2010) or even its craving impairs memory (Palmer et al, 2017). Some studies reported that long-term consumption of caffeine could inhibit hippocampus-dependent learning and memory partially through inhibition of hippocampal neurogenesis (Han et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A high FOK judgment would be made if a person cannot remember the answer to a question now but feels certain of recognizing the answer when seen in the future (e.g., from a list of options). Factors related to memory strength can have different effects on the accuracy of FOK judgments versus JOLs 21,41 ; hence, exercise might have different effects on these two types of judgments.…”
Section: Methodsmentioning
confidence: 99%